Does Society Win or Lose as a Result of Privatization? The Case of Water Sector Privatization in Colombia - Barrera-Osorio, Felipe (2012)
This paper evaluates the impact of water sector privatization in Colombia on access, price and water quality, as well as health outcomes using differences-in-differences methodology. The main findings of the impact of water privatization are: (i) an improvement in the quality of water and an increase in the frequency of the service in privatized urban municipalities for the lower quintiles; (ii) a positive effect on health outcomes in both urban and rural areas; (iii) a negative effect on payment for the lower quintiles; and (iv) strong negative effects on access to water in rural areas. Some of these effects appear in municipalities with better technical capacity.